2012
DOI: 10.1155/2012/960256
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoModelling of Treatment-Induced Tumour Cell Kill: Developments and Advances

Abstract: Mathematical and stochastic computer (in silico) models of tumour growth and treatment response of the past and current eras are presented, outlining the aims of the models, model methodology, the key parameters used to describe the tumour system, and treatment modality applied, as well as reported outcomes from simulations. Fractionated radiotherapy, chemotherapy, and combined therapies are reviewed, providing a comprehensive overview of the modelling literature for current modellers and radiobiologists to ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…Previous studies have also identified that the decrease in NCOA5 expression in esophageal squamous cell carcinoma (ESCC) tissue is associated with the differentiation status of the tumor and the TNM stage, while is not associated with age, sex, weight loss, tumor location or lymph node metastasis (26,27). In addition, the expression of NCOA5 in normal tissues was higher compared with that in tumor tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also identified that the decrease in NCOA5 expression in esophageal squamous cell carcinoma (ESCC) tissue is associated with the differentiation status of the tumor and the TNM stage, while is not associated with age, sex, weight loss, tumor location or lymph node metastasis (26,27). In addition, the expression of NCOA5 in normal tissues was higher compared with that in tumor tissues.…”
Section: Discussionmentioning
confidence: 97%
“…3,[9][10][11] A complete review of in silico radiobiological models is given in Marcu and Harriss-Phillips. 12 Dionysius et al 9,10 introduced the notion of a "geometrical cell," an elementary cubic volume containing a quantity of biological cells, which can be transferred to neighboring geometrical cells in order to maintain cell density within the tumor. In their work, metabolic information from medical imaging can be assigned to the spatially distributed geometrical cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor treatment planning, especially in the case of radiotherapy, uses many different stochastic process calculations, relevant on different time scales, from femtoseconds to years, as reviewed in (16)(17)(18)(19) and in the online AAPS Supplement section S.4.1. The influence on IIV of stochastic fluctuations at the single cell level is considered (16,18); an approach similar to the statistical methods of population PK/PD is also used to analyze IIV [reviewed, e.g., in (20)].…”
Section: Pk/pd Modelingmentioning
confidence: 99%
“…Stochastic process calculations of tumor control probability by radiotherapeutic eradication of cancer cells [reviewed in (16,17,19)] suggested to us analogous analyses of drug dosing regimens: the main novelty in the present paper is transferring a mathematical stochastic process theory technique from radiobiological tumor treatment planning to a PK/PD model of neonatal gentamicin treatment. Differences due to the fact that drugs remain in the body during a period of hours or more had to be taken into account, as did the fact that typically a substantial fraction of bacteria are CFU whereas only a small minority of tumor cells are CFU.…”
Section: Previewmentioning
confidence: 99%